Toll like receptor 7 messenger RNA expression levels in dairy bovines in an outbreak of Foot-and-Mouth disease - Audarya, S.D.; Pattnaik, B.; Sanyal, A.; Mohapatra, J.K. (Buffalo Bulletin, 2017)
Foot-and-Mouth disease (FMD) is an economically most important disease of dairy animals in India. It is caused by Foot-and-Mouth disease virus (FMDV) an under the family Picornaviridae. Pathogenesis and immune responses elicited by FMDV in the processes of infection and vaccination are not completely understood. Toll like receptor 7 (TLR7) is related to inflammation. The present study is aimed at evaluating messenger ribonucleic acid (mRNA) expression of TLR7 in peripheral blood mononuclear cells isolated from dairy animals experiencing an outbreak of FMD in real-time polymerase chain reaction test. TLR mRNA expression level on in an outbreak of FMD is reported probably for the first time. The mRNA expession levels of TLR7 were found at lower side in dairy cattle cows that showed clinical FMD twice as compared to in-contact apparently healthy dairy cattle cows. The present investigation will help in understanding the immune response of bovines against FMD in an outbreak of FMD.